Acute and Chronic Cutaneous Reactions to Ionizing Radiation Therapy. Issue 2 (June 2016) - Bray, Fleta; Simmons, Brian; Wolfson, Aaron; Nouri, Keyvan
Abstract Ionizing radiation is an important treatment modality for a variety of malignant conditions. However, development of radiation-induced skin changes is a significant adverse effect of radiation therapy (RT). Cutaneous repercussions of RT vary considerably in severity, course, and prognosis. When they do occur, cutaneous changes to RT are commonly graded as acute, consequential-late, or chronic. Acute reactions can have severe sequelae that impact quality of life as well as cancer treatment. Thus, dermatologists should be informed about these adverse reactions, know how to assess their severity and be able to determine course of management. The majority of measures currently available to prevent these acute reactions are proper skin hygiene and topical steroids, which limit the severity and decrease symptoms. Once acute cutaneous reactions develop, they are treated according to their severity. Treatments are similar to those used in prevention, but incorporate wound care management that maintains a moist environment to hasten recovery. Chronic changes are a unique subset of adverse reactions to RT that may develop months to years following treatment. Chronic radiation dermatitis is often permanent, progressive, and potentially irreversible with substantial impact on quality of life. Here, we also review the etiology, clinical manifestations, pathogenesis, prevention, and management of late-stage cutaneous reactions to radiotherapy, including chronic radiation dermatitis and radiation-induced fibrosis.